The use of isoniazid syrup for the prevention of tuberculosis in children. - Liliya Todoriko; Ihor Semianiv; Marius Dumitru; Olga Shevchenko; Inga Yeremenchuk; Tetiana Sprinsian (Buletinul Academiei de Ştiinţe a Moldovei: Ştiinţe Medicale, 2019)
The purpose of the study was to conduct a comparative analysis of the use of isoniazid in the form of syrup and tablet for the prevention of tuberculosis in children. Materials and methods. 114 children at risk who were on sanatorium treatment at Chernivtsi children’s sanatorium (Ukraine) were examined for tuberculosis. For chemoprophylaxis in children the drug “Isoniazid” was used: 61 children received the drug in the form of syrup (group 1), 53 - in tablet form (group 2). On the basis of Institute of Pneumology “Marius Nasta” (Romania) 83 children enrolled to the 1 group received preventive therapy with isoniazid in the form of syrup. Results. Significantly lower levels of total protein were reported in 1 group - by 9.6% than in patients in 2 group (р<0.05). Also significantly higher levels of bilirubin - by 17.2 %, ALT (alanine transaminase) - by 19 %, AST (aspartate transaminase) - by 22.4 % and thymol test - by 15.5 % were reported in 2 group compared with 1 group (p <0.05), evidencing that there are preconditions for the development of toxic hepatitis when using isoniazid in tablet form. It is well established that the changes in blood chemistry were much more pronounced in children who received isoniazid tablets and were increasing up to the completion of the course of chemoprophylaxis. Conclusions. The results of complex clinical, laboratory and instrumental study allow us to recommend “Isoniazid” in the form of syrup 100 mg / 5 ml as highly effective drug for the prevention of tuberculosis in children.